Selectivity of the complexation reactions of four regioisomeric methylcamphorquinoxaline ligands with gold(III): X-ray, NMR and DFT investigations. (17th February 2016) - Glišić, Biljana Đ.; Hoffmann, Marcin; Warżajtis, Beata; Genčić, Marija S.; Blagojević, Polina D.; Radulović, Niko S.; Rychlewska, Urszula; Djuran, Miloš I.
Graphical abstract: The reactions of novel methyl-substituted camphorquinoxaline ligands with Au(III) ion resulted in the selective formation of gold(III) complexes. Abstract: Reported are the synthesis, spectral and structural characteristics of new quinoxaline-related regioisomeric ligandsL1 –L4 (1, x, 11, 11-tetramethyl-1, 2, 3, 4-tetrahydro-1, 4-methanophenazine, x  = 7, 8, 9 and 6, respectively) and their mononuclear Au(III) complexes (1 –4 ). Fusion of the camphor moiety to the quinoxaline core made two N-atoms of quinoxaline nonequivalent while the introduction of a methyl-substituent at positions 6–9 enabled a tuning of coordination properties ofL1 –L4 . Gold(III) complexes1 –4 and ligandsL1 –L4 have been studied in detailed by 1D and 2D NMR and the structures of1 –4 have been determined by X-ray crystallography. The results of these analyses revealed a regiospecific coordination of Au(III) to the sterically less hindered N-5 atom (spatially close to the non-substituted bridgehead carbon) ofL1 –L3, and to N-10 (spatially close to the methyl-substituted bridgehead carbon) ofL4 . The results of DFT calculations shed light on disparate coordination modes ofL1 –L4 toward the AuCl3 fragment and explain formation of single coordination products in high yield.